A Multiple Streams Analysis of Institutional Innovation in Forest Watershed Governance. Issue 6 (28th November 2019) - Huber‐Stearns, Heidi R.; Schultz, Courtney; Cheng, Antony S.
Abstract: Increasingly severe wildfires have focused attention on forested watershed vulnerabilities, causing significant changes to policies and governance. We utilized the Multiple Streams Approach (MSA) to understand institutional innovations of federal agency–large water provider partnerships in Colorado to protect watersheds through joint planning and funding. Ambiguous problem definition and focusing events were significant aspects of these partnerships. We interviewed individuals in the partnerships, with MSA ideas of how solutions to policy problems develop, and the role of policy entrepreneurs. We found that wildfires served as focusing events, creating space and time for learning, collaboration and new problem framing, increased political attention, and institutional innovation. In this study, windows of opportunity stayed open longer, policy entrepreneurs and agencies played larger roles in communication and coupling streams and the context of fast‐moving, unpredictable ecological crises changed responses to issues. Our findings also have implications for broader policy studies and environmental governance scholarship. 摘要: 一项关于森林流域治理中制度创新的多源流分析: 日益严重的野火灾害已将关注聚焦于森林流域脆弱性，并引起政策和治理方面的显著变化。我们使用多源流措施（MSA），以期理解科罗拉多州联邦机构和大型供水商伙伴关系的制度创新，该创新通过联合计划和资金提供来保护流域。模糊的问题定义和焦点事件曾是伙伴关系的重要方面。我们就政策问题的解决措施如何发展、政策企业家发挥的作用等相关MSA观点，采访了伙伴关系中的个人。作者发现，野火作为焦点事件，创造了用于学习、协作、新问题构建的时空，提高了政治关注和制度创新。本研究中，机会之窗的开启时间更常，政策企业家和政府机构在传播和源流耦合中发挥了更大的作用，发展迅速、无法预测的生态危机背景改变了对问题的响应。研究发现对更广范围的政策研究和环境治理学术具有意义。 Resumen: Un análisis de múltiples flujos de innovación institucional en la gobernanza de cuencas forestales: Los incendios forestales cada vez más tumbas han centrado la atención en las vulnerabilidades de las cuevas forestales, lo que ha provocado cambios peligrosos en las políticas y la gobernanza. Específicamente el Enfoque de múltiples corrientes (MSA) para comprender las innovaciones institucionales de las asociaciones de proveedores de agua de grandes agencias federales en Colorado para proteger las cuencas hidrográficas a través de la planificación y financiación conjuntas. La definición ambigua de problemas y los eventos de enfoque fueron aspectos específicos de estas asociaciones. Entrevistamos a personas en las alianzas, con ideas de MSA sobre cómo se resolverán las soluciones a los problemas de política y el papel de los emprendedores de políticas. Descubriendo que los incendios forestales sirvieron como eventos de enfoque, creando espacio y tiempo para el aprendizaje, la colaboración y la formulación de nuevos problemas, mayor atención política e innovación institucional. En este estudio, las ventanas de oportunidad permanecen abiertas por más tiempo, los emprendedores políticos y las agencias juegan un papel más importante en la comunicación y las corrientes de acoplamiento, y el contexto de crisis ecológicas impredecibles y de cambio rápido, las respuestas a los problemas Nuestros hallazgos también tienen implicaciones para estudios de política más amplios y estudios de gobernanza ambiental.